Efektifitas pendidikan kesehatan terhadap peningkatan pengetahuan keluarga tentang infeksi Saluran pernapasan akut (ispa) - Weni - Utari; Arneliwati - -; Riri - Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aimed to determine the effectiveness of health education for increasing family’s knowledge about acute respiratory infections. This was a quasi-experimental research that used control group with the implementation of health education. Participant of this research were 30 families that was divided into 15 experiment and 15 control groups. The data were analyzed by Wilcoxon and Mann Whitney test. The results of this study showed a significant increase in knowledge of acute respiratory infections for the experimental group with p value < α (0,001<0,05). Based on the results, the health providers should provide health education using audiovisual media for the family. Key words : Health education, knowledge, family, acute respiratory infections